2012
DOI: 10.1002/ange.201205498
|View full text |Cite
|
Sign up to set email alerts
|

Using Host–Guest Complexation to Fold a Flexible Linear Organic String: Kinetically Controlled Syntheses of [3]Catenanes and a Five‐Membered Molecular Necklace

Abstract: Ringe und Ketten: Drei [3]Catenane und eine fünfteilige Perlenkette ([5]MN) mit bis zu 60‐ bzw. 92‐gliedrigen Ringen als zentralen Einheiten wurden synthetisiert. Die Synthese ging von den entsprechenden Komplexen aus, in denen die eingefädelten flexiblen linearen Gäste in ungefähr rechten Winkeln gebogen waren, um kinetisch kontrollierte Makrocyclisierungen zu erleichtern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Removal of the tosyl protecting group of [ 3 ][PF 6 ] under acidic conditions, followed by anion exchange, gave the threadlike salt [ 4 ‐H][2 PF 6 ] in 63 % yield. Addition of stopper unit 2 to a mixture of the molecular cage 5 (13 m M ) and threadlike salt [ 4 ‐H][2 PF 6 ] (26 m M ) in CH 3 NO 2 afforded the corresponding [2]rotaxane [ 6 ‐H][3 PF 6 ] in 40 % yield after ion exchange and chromatography (Scheme ) 12…”
Section: Resultsmentioning
confidence: 99%
“…Removal of the tosyl protecting group of [ 3 ][PF 6 ] under acidic conditions, followed by anion exchange, gave the threadlike salt [ 4 ‐H][2 PF 6 ] in 63 % yield. Addition of stopper unit 2 to a mixture of the molecular cage 5 (13 m M ) and threadlike salt [ 4 ‐H][2 PF 6 ] (26 m M ) in CH 3 NO 2 afforded the corresponding [2]rotaxane [ 6 ‐H][3 PF 6 ] in 40 % yield after ion exchange and chromatography (Scheme ) 12…”
Section: Resultsmentioning
confidence: 99%
“…The early research of molecular necklace could be traced back to the work reported by Sauvage et al, who generated a mixture of molecular necklaces by accident in a very low yield and characterized their structures by using electrospray ionization mass spectrometry (ESI-MS) 29 . Moreover, Stoddart et al [30][31][32] , Chiu et al 33 , Grubbs et al 34 , and Wu et al 35 also reported a series of molecular necklaces through covalent synthesis assisted by weak donor-acceptor π-π interactions or dynamic covalent chemistry, but the yield was also relatively low. Notably, Kim and coworkers realized the highly efficient assembly of molecular necklaces by taking advantage of coordination bonds and cucurbituril-based host-guest chemistry, which is definitely a big breakthrough [36][37][38] .…”
mentioning
confidence: 99%